Fc receptor engagement of HIV-1 Env-specific antibodies in mothers and infants predicts reduced vertical transmission - Barrows, Brittani M.; Krebs, Shelly J.; Jian, Ningbo; Zemil, Michelle; Slike, Bonnie M.; Dussupt, Vincent; Tran, Ursula; Mendez-Rivera, Letzibeth; Chang, David; O’Sullivan, Anne Marie; Mann, Brendan; Sanders-Buell, Eric; et al. (Frontiers in Immunology, 2022)
Infants acquire maternal antibodies by Fc receptor transcytosis across the placenta during pregnancy. Fc receptors are expressed on immune cells and are important for activation of effector cell functions. In this study, we evaluated Fc receptor engagement and ADCC activity of plasma binding antibodies from HIV-infected mothers and their HIV-infected or uninfected infants to identify factors that may contribute to protection from HIV vertical transmission. HIV-specific binding and Fc receptor engagement of plasma antibodies varied between mothers by transmission status and infants by infection status. Non-transmitting (NT) mothers and HIV-uninfected infants had antibodies with higher neonatal Fc receptor (FcRn) and FcyR engagement, as compared to transmitting (T) mothers and HIV+ infants, respectively. A significant inverse correlation between plasma antibody FcRn and FcyR engagement was observed for T mothers, but not NT mothers. Conversely, a significant direct correlation was observed between plasma antibody FcRn and FcyR engagement for HIV- infants, but not for HIV+ infants. Consequently, we observed significantly higher plasma antibody ADCC potency and breadth in HIV- infants, as compared to HIV+ infants. However, no differences in overall ADCC potency and breadth were observed between mothers. FcRn-engagement of HIV-specific antibodies in both mothers and infants predicted a lack of vertical transmission of HIV. This study indicates that HIV-uninfected infants acquire HIV-specific antibodies with greater Fc receptor engagement and thus, greater ADCC capacity.